2019
DOI: 10.1002/da.22952
|View full text |Cite
|
Sign up to set email alerts
|

White matter integrity and functional predictors of response to repetitive transcranial magnetic stimulation for posttraumatic stress disorder and major depression

Abstract: Background: Recent evidence suggests that therapeutic repetitive transcranial magnetic stimulation (TMS) is an effective treatment for pharmacoresistant posttraumatic stress disorder (PTSD) and comorbid major depressive disorder (MDD). We recently demonstrated that response to 5 Hz TMS administered to the dorsolateral prefrontal cortex was predicted by functional connectivity of the medial prefrontal (MPFC) and subgenual anterior cingulate cortex (sgACC). This functionallydefined circuit is a novel target for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Importantly, rTMS has demonstrated an ability to affect white matter tracts within the stimulated hemisphere [ 121 , 122 ]. Recent studies have demonstrated hemispheric differences in white matter topography underlying key cortical areas involved in mood and anxiety regulation [ 123 , 124 , 125 ], further suggesting that differences in structural connectivity between the left and right hemispheres in MDD likely have bearing on the efficacy of rTMS. This may be especially true in older adults, where it has been proposed that MDD is the result of age related degradation of white matter tracts [ 126 ].…”
Section: Specialization Vs Valencementioning
confidence: 99%
“…Importantly, rTMS has demonstrated an ability to affect white matter tracts within the stimulated hemisphere [ 121 , 122 ]. Recent studies have demonstrated hemispheric differences in white matter topography underlying key cortical areas involved in mood and anxiety regulation [ 123 , 124 , 125 ], further suggesting that differences in structural connectivity between the left and right hemispheres in MDD likely have bearing on the efficacy of rTMS. This may be especially true in older adults, where it has been proposed that MDD is the result of age related degradation of white matter tracts [ 126 ].…”
Section: Specialization Vs Valencementioning
confidence: 99%
“…Repetitive transcranial magnetic stimulation (rTMS) is a non-invasive intervention widely used to treat several psychiatric disorders, such as major depressive disorder (MDD) ( Miron et al, 2019 ), posttraumatic stress disorder (PTSD) ( Philip et al, 2019 ) and schizophrenia ( Jiang et al, 2019 ). White matter integrity and function is a predictor for the treatment response of rTMS for PTSD and MDD ( Barredo et al, 2019 ), and low-intensity TMS promote the survival and maturation of newborn oligodendrocytes in the adult mouse brain ( Cullen et al, 2019 ). Moreover, rTMS has also been shown to be beneficial in treating demyelinating disorders, such as Alzheimer’s disease and multiple sclerosis ( San et al, 2019 ; Chou et al, 2020 ); thus, the protective effects of myelin might be involved in the beneficial effects of rTMS.…”
Section: Introductionmentioning
confidence: 99%
“…Recent results indicate that both structural [ 53 ] and functional connectivity MRI parameters [ 54 ] may contain relevant information concerning TBS treatment responses in depression. Regarding the understanding of mechanisms and response predictors of TBS therapy, there is no doubt that individual network structure and activity [ 55 , 56 ] as well as the genetic and epigenetic make-up [ 57 ] critically interacts with the clinical effect of TBS in depression.…”
Section: Discussionmentioning
confidence: 99%